Presence and removal of a contaminating NADH oxidation activity in recombinant maltose-binding protein fusion proteins expressed in Escherichia coli. (April 2012) - Guo, Fengguang; Zhu, Guan
We observed the presence of contaminating NADH oxidation activity in maltose binding protein (MBP) fusion proteins expressed in Escherichia coli and purified using conventional amylose resin-based affinity chromatography. This contaminating NADH oxidation activity was detectable with at least four different enzymes from Cryptosporidium parvum expressed as MBP-fusion proteins (i.e., an enoyl-reductase domain from a type I fatty acid synthase, a fatty acyl-CoA binding protein, the acyl-ligase domain from a polyketide synthase, and a putative thioesterase), regardless of their NADH dependence. However, contaminating NADH oxidation activity was not present when fusion proteins were engineered to contain a His-tag and were purified using a Ni-NTA resin-based protocol. Alternatively, for proteins containing only an MBP-tag, the contaminating activity could be eliminated through the addition of 0.1% Triton X-100 and 2% glycerol to the column buffer during homogenization of bacteria and first column wash, followed by an additional wash and elution with regular column and elution buffers. Removal of the artifactual activity is very valuable in the study of enzymes using NADH as a cofactor, particularly when the native activity is low or the recombinant proteins are inactive.